2020
DOI: 10.1109/access.2020.3019885
|View full text |Cite
|
Sign up to set email alerts
|

Fully Projection-Free Proximal Stochastic Gradient Method With Optimal Convergence Rates

Abstract: Proximal stochastic gradient plays an important role in large-scale machine learning and big data analysis. It needs to iteratively update models within a feasible set until convergence. The computational cost is usually high due to the projection over the feasible set. To reduce complexity, many projection-free methods such as Frank-Wolfe methods have been proposed. However, those projection-free methods have to solve a linear programming problem for every update of models which still leads to high computatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Optimization problems of this kind are not new, and many approximate solutions have been proposed in the past, including projected gradient algorithms [3], conditional gradient descent (alias Frank-Wolfe algorithms) [24,32], and other projection-free stochastic methods [41]. However, we found that one can take advantage of the structure of the problem (12) to induce a precise and average-case efficient algorithmic solution to (11).…”
Section: Generalized Credal Learningmentioning
confidence: 94%
“…Optimization problems of this kind are not new, and many approximate solutions have been proposed in the past, including projected gradient algorithms [3], conditional gradient descent (alias Frank-Wolfe algorithms) [24,32], and other projection-free stochastic methods [41]. However, we found that one can take advantage of the structure of the problem (12) to induce a precise and average-case efficient algorithmic solution to (11).…”
Section: Generalized Credal Learningmentioning
confidence: 94%